Valency and density matter: Deciphering impacts of immunogen structures on immune responses against a tumor associated carbohydrate antigen using synthetic glycopolymers. (September 2016) - Qin, Qian; Yin, Zhaojun; Wu, Xuanjun; Haas, Karen M.; Huang, Xuefei
Abstract: For successful carbohydrate based anti-cancer vaccines, it is critical that B cells are activated to secret antibodies targeting the tumor associated carbohydrate antigens (TACAs). Despite the availability of many TACA based constructs, systematic understanding of the effects of structural features on anti-glycan antibody responses is lacking. In this study, a series of defined synthetic glyco-polymers bearing a representative TACA, i.e., the Thomsen-nouveau (Tn) antigen, have been prepared to probe the induction of early B cell activation and antibody production via a T cell independent mechanism. Valency and density of the antigen in the polymers turned out to be critical. An average of greater than 6 Tn per chain was needed to induce antibody production. Glycopolymers with 40 antigens per chain and backbone molecular weight of 450 kDa gave the strongest stimulation to B cells in vitro, which correlated well with its in vivo activity. Deviations from the desired valency and density led to decreased antibody production or even antigen specific B cell non-responsiveness. These findings provide important insights on how to modulate anti-TACA immune responses facilitating the development of TACA based anti-cancer vaccines using glycopolymers. Graphical abstract: The valency and the spacing between the antigens are critical for antibody generation against a tumor associated carbohydrate antigen.